Development of a consensus approach for botanical safety evaluation – A roundtable report. (10th October 2019) - Galli, Corrado L.; Walker, Nigel J.; Oberlies, Nicholas H.; Roe, Amy L.; Edwards, James; Fitzpatrick, Suzanne; Griffiths, James C.; Hayes, A. Wallace; Mahony, Catherine; Marsman, Daniel S.; O'Keeffe, Lara
Abstract: Botanical safety science continues to evolve as new tools for risk assessment become available alongside continual desire by consumers for "natural" botanical ingredients in consumer products. Focusing on botanical food/dietary supplements a recent international roundtable meeting brought together scientists to discuss the needs, available tools, and ongoing data gaps in the botanical safety risk assessment process. Participants discussed the key elements of botanical safety evaluations. They provided perspective on the use of a decision tree methodology to conduct a robust risk assessment and concluded with alignment on a series of consensus statements. This discussion highlighted the strengths and vulnerabilities in common assumptions, and the participants shared additional perspective to ensure that this end-to-end safety approach is sufficient, actionable and timely. Critical areas and data gaps were identified as opportunities for future focus. These include, better context on history of use, systematic assessment of weight of evidence, use of in silico approaches, inclusion of threshold of toxicological concern considerations, individual substances/matrix interactions of plant constituents, assessing botanical-drug interactions and adaptations needed to apply to in vitro and in vivo pharmacokinetic modelling of botanical constituents.